169 Antisaccade task as a biomarker in MND. Issue 3 (9th February 2012) - Sharma, R; Hicks, S; Berna, C; Kennard, C; Talbot, K; Turner, M R
Abstract : Background: MND is a multiple system neurodegenerative disorder sharing clinicopathological features with frontotemporal dementia. The normal saccade generating network has overlap with cortical regions consistently involved in MND, and the relative sparing of brainstem nuclear oculomotor functions makes eye-tracking a uniquely practical way to explore this extramotor pathology. Meyhods: ALS (n=31) and PLS patients (n=5) and age-similar healthy controls (n=26) were tested using the EyeLink® eye-tracker. The tasks included a prosaccade ("look towards"), antisaccade ("look away"), word and picture-cued visual search tasks, and an oculomotor version of the Trail-making test. Results: Both antisaccade latency and error rates were markedly increased in both ALS and PLS patient groups compared to controls (p<0.001), and error rates in the PLS group were increased compared to the ALS group (p<0.05). Word and picture-cued searches, and TMT performance were also slower, with ALS and PLS patients making more fixations per target (all p<0.01). There were no significant differences in prosaccade task performance between any groups. Conclusions: Eye-tracking has significant potential as an objective, quantifiable biomarker of extramotor pathology in MND. The antisaccade task has attraction as a non-invasive diagnostically supportive biomarker that could be adapted to a portable saccadometer for routine clinical use.